The Intrinsic Study of Shakespeare â€œThe Tragedy of Julius Caesar and Itâ€™s Implication on the Teaching of Reading Comprehension - Imanudin, Jajat (Jurnal Ilmiah Dozen Globalindo, 2019)
This study was aimed to analyse the intrinsic study ofShakespeareâ€™s the tragedyof Julius caesar and itâ€™s implication on the teaching of reading comprehension.In understanding the literature, there are two main factors that are appreciatednamely intrinsic and extrinsic. In this study the writer limited the problem on theintrinsic study in the drama entitle â€œThe Tragedy of Julius Caesarâ€. Theintrinsic study includes theme, plot, character, setting and language. The writerchose the script of the drama as the population and chose the drama entitleâ€œThe Tragedy of Julius Caesarâ€ as the sample of the research and focused onthe intrinsic study. This study used purposive sampling technique. It was basedon the point ofview of the writer. The sampling technique that the writer choseaccording to the goal of the research it was research on the intrinsic study of thescript.the method used in this study was descroptive method. The writercollected the data from the script of the drama â€œThe Tragedy of Julius Caesarâ€,analyzed, and summarized the result of the analysis. The instrument in this studywas the text of the drama entitle â€œThe Tragedy of Julius Caesarâ€. Then analyzedused content analysis technique. Based on the result used content analysistechnique, the writer concluded that the script of the drama â€œThe Tragedy ofJulius Caesarâ€ consisted the intrinsic study and it can be the material in theteaching reading comprehension.Key words: intrinsic study, implication, reading comprehension